Accident detection system and method for accident detection - Alkandari, Abdulrahman; Taha Alshaikhli, Imad Fakhri (2014)
The accident detection system is a smart system which uses fuzzy (probabilistic) logic to determine an approximate location of an accident or other traffic impediment based on sensors, such as wired or wireless sensors, scanning, detecting, and reporting the traffic flow across a number of traffic lanes and a cross-section of a roadway. The sensors in the accident detection system detect an area where traffic appears impeded based on the calculation of moving vehicles in nearby lanes or areas in a proximate location to the area where traffic appears impeded. The accident detection system utilizes a series of strategically placed sensors connected through the wireless or wired sensor network, which detects vehicles in real time to acquire data such as an impediment in traffic flow, such as an accident, an inoperative vehicle, and similar traffic disturbances.